Effectiveness of a randomized intervention by a geriatric team in frail hospital inpatients in non‐geriatric settings: FRAILCLINIC project - Marta Checa‐López; Alba Costa‐Grille; Alejandro Álvarez‐Bustos; Jose A. Carnicero‐Carreño; Alan Sinclair; Angelo Scuteri; Francesco Landi; Juan José Solano‐Jaurrieta; Srikanth Bellary; Leocadio Rodríguez‐Mañas (Wiley, 2024)
Abstract Background Little research has been undertaken on the benefits of frailty management within different hospital settings. The objective of this study is to provide evidence on the viability and effectiveness of frailty management in non‐geriatric hospital settings on mortality and functional decline after discharge. Methods Data from the FRAILCLINIC (NCT02643069) study were used. FRAILCLINIC is a randomized controlled trial developed in non‐geriatric hospital inpatient settings (emergency room, cardiology and surgery) from Spain (2), Italy (2) and the United Kingdom (1). Inpatients must met frailty criteria (according to the Frailty Phenotype and/or FRAIL scale), ≥75 years old. The control group (CG) received usual care. The intervention group (IG) received comprehensive geriatric assessment (CGA) and a coordinated intervention consisting in recommendations to the treating physician about polypharmacy, delirium, falls, nutrition and physical exercise plus a discharge plan. The main outcomes included functional decline (worsening ≥5 points in Barthel Index) and mortality at 3 months. We used multivariate logistic regression models adjusted by age, gender and the Charlson index. Intention‐to‐treat (ITT) and per‐protocol (PP) analyses were used. Results Eight hundred twenty one participants (IG: 416; mean age 83.00 ± 4.91; 51.44% women; CG: 405; mean age 82.46 ± 6.03; 52.35% women) were included. In the IG, 77.16% of the participants followed the geriatric team's recommendations as implemented by the treating physicians. The intervention showed a benefit on functional decline and mortality [OR: 0.67(0.47-0.96), P‐value 0.027 and 0.29(0.14-0.57), P‐value < 0.001, respectively) when fully followed by the treating physician. A trend to benefit (close to statistical significance) in functional decline and mortality were also observed when any of the recommendations were not followed [OR (95% CI): 0.72 (0.51-1.01), P‐value: 0.055; and 0.64 (0.37-1.10), P‐value: 0.105, respectively]. Conclusions An individualized intervention in frail in‐patients reduces the risk of functional deterioration and mortality at 3 months of follow‐up when a care management plan is designed and followed.